Are fish larvae contaminated before they start eating? First evidence of microplastic contamination in the yolk-sac of wild fish larvae - Rodrigues, Sabrina M.; Espincho, Francisca; Elliott, Michael; Almeida, C. Marisa R.; Ramos, Sandra (Frontiers in Marine Science, 2025)
Microplastics (MPs) ingestion in wild fish during the early stages remains a field with scarce information and contradictory findings in laboratory studies. This study evaluated whether MPs contamination of larval fish stages begins at the commencement of the exogenous feeding phase and whether different species and ontogenetic development stages exhibit different profiles of MPs contamination. We assessed, for the first time, the presence of MPs in the larval stages of two species: the European sardine (Sardina pilchardus), a marine migrant species, and the common goby (Pomatoschistus microps), an estuarine resident species, inhabiting the Douro Estuary (NW Portugal). In both species, MPs were found even in the yolk-sac stage, when fish larvae still have endogenous feeding and do not actively prey on other organisms. This illustrates that fish larvae are already contaminated at a stage where the mouth is still not fully open, further indicating that MPs were not actively ingested. MPs contamination did not vary between species or throughout the ontogenetic development stages, showing similar levels of contamination and MPs contamination profiles. This novel study provides relevant insights into MPs contamination processes, showing that MPs contamination can occur early in the life cycle of fishes, from hatching onwards. Furthermore, the presence of MPs in fish larvae appears to be more dependent on the MPs that are in higher abundance in the surrounding water than fish larvae preferences or ecological guild, physical characteristics, or even the ontogenetic developmental stage.